2020
DOI: 10.1038/s41467-020-16096-w
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitinated-PCNA protects replication forks from DNA2-mediated degradation by regulating Okazaki fragment maturation and chromatin assembly

Abstract: Upon genotoxic stress, PCNA ubiquitination allows for replication of damaged DNA by recruiting lesion-bypass DNA polymerases. However, PCNA is also ubiquitinated during normal S-phase progression. By employing 293T and RPE1 cells deficient in PCNA ubiquitination, generated through CRISPR/Cas9 gene editing, here, we show that this modification promotes cellular proliferation and suppression of genomic instability under normal growth conditions. Loss of PCNA-ubiquitination results in DNA2-dependent but MRE11-ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
147
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(161 citation statements)
references
References 74 publications
(121 reference statements)
14
147
0
Order By: Relevance
“…In addition to damaged-induced ubiquitylation, PCNA was shown to be mono-ubiquitylated during replication of undamaged sperm chromatin ( Leach and Michael, 2005 ). A recent report suggests that this is also likely the case in human cells ( Thakar et al., 2020 ), and our data generated during replication of undamaged plasmids agree with these findings. Although the significance of damage-independent PCNA mono-ubiquitylation remains unclear, RFWD3 depletion did not affect it, suggesting independent mechanisms for inducing PCNA ubiquitylation at the fork during unstressed replication versus at ssDNA gaps upon DNA damage and RFWD3 regulating only the latter of the two.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to damaged-induced ubiquitylation, PCNA was shown to be mono-ubiquitylated during replication of undamaged sperm chromatin ( Leach and Michael, 2005 ). A recent report suggests that this is also likely the case in human cells ( Thakar et al., 2020 ), and our data generated during replication of undamaged plasmids agree with these findings. Although the significance of damage-independent PCNA mono-ubiquitylation remains unclear, RFWD3 depletion did not affect it, suggesting independent mechanisms for inducing PCNA ubiquitylation at the fork during unstressed replication versus at ssDNA gaps upon DNA damage and RFWD3 regulating only the latter of the two.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the Ki67 staining results, our previous study showed that there was a significant reduction of PCNA levels in MnTE-2-PyP-treated prostate cancer cells with or without radiation [95]. PCNA is a key component in cell cycle progression, especially in S phase for precise DNA replication and DNA damage repair [192][193][194][195]. acetylation on K403 of G6PD will prevent the formation of the functional dimer and reduces G6PD activity, but acetylation on K76 and K294 of 6PGD will increase 6PGD activity [196][197][198][199].…”
Section: Mnte-2-pyp Inhibits Gr Activity By Depleting Nadph Poolsupporting
confidence: 77%
“…Therefore, we measured the levels of chromatin-bound PCNA-Ub as an indicator of the relative number of active replication forks. Although baseline PCNA-Ub is significantly lower than in HCT116 cancer cells, it is detectable under unperturbed conditions 34 . Because of this, we were able to determine that MCM10 mutants had significantly lower PCNA-Ub (Fig.…”
Section: Resultsmentioning
confidence: 88%